2013
DOI: 10.1002/lt.23654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of post-liver transplant new-onset heart failure

Abstract: Objectives of this study were (1) to evaluate preoperative predictors of systolic and diastolic heart failure in patients undergoing liver transplantation (LT) and (2) to describe the prognostic implications of systolic and diastolic heart failure in these patients. The onset of heart failure after orthotopic LT remains poorly understood. Data were obtained for all LT recipients between January 2000 and December 2010. The primary outcome was post-LT heart failure: systolic (ejection fraction 50%), diastolic, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 40 publications
7
90
0
1
Order By: Relevance
“…The incidence of systolic HF after OLT reported in our study is similar to that reported by others . Qureshi et al reported an incidence of 7% among 970 patients after a median follow‐up of 5 years, a quarter among who developed HF within a week of OLT. In their study, the presence of grade 3 DD and certain cardiovascular risk factors (hypertension and diabetes) before OLT were associated with systolic HF.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence of systolic HF after OLT reported in our study is similar to that reported by others . Qureshi et al reported an incidence of 7% among 970 patients after a median follow‐up of 5 years, a quarter among who developed HF within a week of OLT. In their study, the presence of grade 3 DD and certain cardiovascular risk factors (hypertension and diabetes) before OLT were associated with systolic HF.…”
Section: Discussionsupporting
confidence: 90%
“…Calcineurin inhibitors, a common antirejection medication used after OLT, have been associated with DD . On the other hand, preoperative beta blocker use was found to be protective for HF after OLT …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qureshi et al . has recently reported that a QTc interval >450 is a predictor of post‐LT systolic heart failure .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not find coronary artery disease or elevated blood pressure to be a significant risk factor for heart failure in this population. 4 Seventeen cases developed heart failure within the first 30 days, and 9 cases (>50%) suffered from perioperative myocardial infarction. Only 12 of these 17 cases developed systolic heart failure, and they eventually included all 9 cases with perioperative myocardial infarction.…”
mentioning
confidence: 99%